2020
DOI: 10.26434/chemrxiv.12199610.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drug Repurposing Against SARS-CoV-2 Using E-Pharmacophore Based Virtual Screening and Molecular Docking with Main Protease as the Target

Abstract: Since its first report in December 2019 from China the COVID-19 pandemic caused by the beta-coronavirus SARS-CoV-2 has spread at an alarming pace infecting about 26 lakh, and claiming the lives of more than 1.8 lakh individuals across the globe. Although social quarantine measures have succeeded in containing the spread of the virus to some extent, the lack of a clinically approved vaccine or drug remains the biggest bottleneck in combating the pandemic. Drug repurposing can expedite the process of drug develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hence, it is less likely that a drug against SARS-CoV-2 M pro would cross-react with a human protease. Using M pro as the target, our group had recently reported a subset of drugs from the SuperDrug2 database which showed potential to be used against SARS-CoV-2 [16].In the present study, we report the virtual screening of the DrugBank databse, a larger database of drugs using the method of E-pharmacophore modeling and dockingto identify compoundsthat would inhibit M pro and hence could be repurposed against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is less likely that a drug against SARS-CoV-2 M pro would cross-react with a human protease. Using M pro as the target, our group had recently reported a subset of drugs from the SuperDrug2 database which showed potential to be used against SARS-CoV-2 [16].In the present study, we report the virtual screening of the DrugBank databse, a larger database of drugs using the method of E-pharmacophore modeling and dockingto identify compoundsthat would inhibit M pro and hence could be repurposed against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…In the active research for finding molecule that can treat COVID-19, two approaches are currently being used. One is to identify new uses for FDA-approved drugs (drug repurposing) [5][6], while the other one is to identify from plants biodiversity potential inhibitors or phytochemicals of SARS-CoV-2's main protease using molecular modeling approaches [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that αketoamides are effective inhibitors against the main protease [4,5]. Numerous studies have also discovered that some approved drugs may inhibit enzyme activity [6][7][8]. However, the pharmacophore site of the enzyme is still not clear.…”
Section: Introductionmentioning
confidence: 99%